Hypothalamic lipophagy and energetic balance - Singh, Rajat (Impact Journals LLC, 2011)
Autophagy is a conserved cellular turnover process that degrades unwanted cytoplasmic material within lysosomes. Through “in bulk” degradation of cytoplasmic proteins and organelles, including lipid droplets, autophagy helps provide an alternative fuel source, in particular, when nutrients are scarce. Recent work demonstrates a role for autophagy in hypothalamic agouti-related peptide (AgRP) neurons in regulation of food intake and energy balance. The induction of autophagy in hypothalamic neurons during starvation mobilizes neuronal neutral lipids to generate neuron-intrinsic free fatty acids that serve to upregulate fasting-induced AgRP levels. Blocking autophagy in AgRP neurons in mice reduces fasting-induced food intake, and increases constitutive levels of anorexigenic hypothalamic proopiomelanocortin and its cleavage product α-melanocyte stimulating hormone. The energetic consequences of these molecular events are decreased body weight and reduced adiposity. The present article discusses this recent finding, as well as considers possible future directions that may help better understand how neuronal autophagy, and its possible reduction during aging, may affect whole body energy balance.